Built environment and leisure satisfaction: The role of commute time, social interaction, and active travel. (October 2019) - Mouratidis, Kostas
Abstract: Leisure satisfaction is an important life domain with significant contribution to health and well-being. However, little evidence exists on how the built environment influences leisure satisfaction. This paper develops, applies, and tests a new model on the built environment and leisure satisfaction. The paper relies on survey, interview, and spatial data collected within Oslo metropolitan area and employs structural equation modeling (SEM) combined with qualitative analysis. Findings suggest that built environment characteristics can significantly affect leisure activities and leisure satisfaction. Urban greenness and local amenities are found to positively influence leisure satisfaction. High neighborhood density and proximity to city center are also found to influence leisure satisfaction, but they do it indirectly. Compact built environments exert a negative indirect impact on leisure satisfaction via reduced urban green space, and positive indirect impacts via higher access to local amenities, shorter commutes, and increased social interaction. Short commute time, social interaction, active travel such as walking and cycling, and overall physical activity are all found to positively contribute to leisure satisfaction. Based on all these findings, the paper finally discusses land use and transport policy implications for improving leisure satisfaction, health, and well-being in urban regions.